Distributed leadership in educational organizations in Madrid: case study - Ingrid del Valle García Carreño (Universidade Estadual Paulista Júlio de Mesquita Filho, 2021)
The objective of this research is to describe the four dimensions of distributed leadership (DL) to know the perception of the directors of two of the public and primary education centers in Madrid, Spain. METHOD. The research design is a qualitative study with a case study. The main objective is to understand the perception of four dimensions of DL and the actions of the Director through two representative cases of public schools. The techniques used to gather information were documentary analysis, in-depth structured interviews (with their respective guide) and observation. The guide allows you to collect the perception developed by the directors in the context studied, and to know the relevance they grant them. RESULTS AND DISCUSSION. The results found are very broad and correspond to the two directors surveyed.